Competences in research and scientific production in doctors from hospitals and health institutes from Lima, Peru - Rojas-Cama, Luis F. (2022)
Introduction. Scientific production in the country can be promoted by identifying its relationship with the competencies required to investigate in hospitals and health institutes of Lima. Objective. To determine the relationship between competences in research and scientific production in Hospital Physicians and Health Institutes of Lima, Peru. Methods. A quantitative, analytical and correlational study was carried out, which included 100 doctors from hospitals and health institutes. The improved and validated instrument called “Test to evaluate research competencies” was applied and data was collected about the scientific production of doctors. Results. The mean age was 39 ± 8 years, the predominant population was male, married, with care work, contracted and with a medical specialty. Significant differences were found in the theoretical and cognitive competencies of doctors from Hospitals and Health Institutes (p = 0,005 and p = 0,001 respectively). The publications of physicians from institutes were significantly higher than those from hospitals (OR: 5,12; 95% CI: 2-12,9; p = 0,0004). Cognitive competence was correlated to the scientific production of doctors (r = 0,4, p <0,001). Conclusions. Cognitive competence and subcompetencies in research (self-regulation, tolerance to uncertainty, critical attitude, openness and curiosity) were related to scientific production in physicians from hospitals and health institutes of Lima.